GEOGRAPHY OF ASCARIASIS IN BELARUS: CULTURAL AND ANTHROPOLOGICAL ASPECTS (PART 2) - S. V. Kandrychyn (Российский паразитологический журнал, 2019)
Objective of research: The epidemiological analysis of spatial distribution of ascariasis among the population in different regions of Belarus taking into account anthropological and cultural aspects. The studies on regional differences in ascariasis conducted in the USSR were focused rather on climatic, hygienic and economic factors and did not consider the causative role of cultural and anthropological factors in epidemiological process. The study is aimed at comparing regional indices of ascariasis with the previously defined two spatial historical gradient manifested in Belarus. Materials and methods: The effect of social and cultural spatial gradient was assessed by correlating differences in ascariasis morbidity between eastern and western regions of Belarus. Thus, the effect of ethnic and anthropological spatial gradient was considered in comparison of epidemiological indices between the Brest region situated on the south-west of the country and Vitebsk regions on the northeast. The analysis was performed with the historical perspective; the regional epidemiological statistics were compared in two periods 1970-1989 and 2000-2014. The work is based on the national Ministry of Health’ official annual statistics data. Results and discussion: The analysis showed that the differentiation trend in distribution of ascariasis in Belarus correlates both with historical-cultural and anthropological spatial gradients. The identified pattern of regional differentiation allows evaluating the complex effect of sociocultural and anthropogenic components on epidemiological features of ascariasis.